Evaluation of the Dissemination, Implementation, and Sustainability of the "Partnership for Health" Intervention. Issue 6 (November 2016) - August, Euna M.; Hayek, Samah; Casillas, Daniel; Wortley, Pascale; Collins, Charles B.
Abstract : This report uses a cross-sectional, mixed-methods design to describe the evaluation of the dissemination, implementation, and sustainability of the Partnership for Health Intervention. Abstract : Partnership for Health (PfH) is an evidence-based, clinician-delivered HIV prevention program conducted in the United States for HIV-positive patients. This intervention strives to reduce risky sexual behaviors through provider-patient discussions on safer sex and HIV status disclosure. A cross-sectional, mixed-methods design was used to evaluate the dissemination and implementation of PfH, including training evaluations, an online trainee survey, and interviews with national trainers for PfH. Descriptive statistics were calculated with the categorical data, whereas thematic analysis was completed with the qualitative data. Between 2007 and 2013, PfH was disseminated to 776 individuals from 104 different organizations in 21 states/territories. The smallest proportion of trainees was physicians (6.9%). More than three-fourths of survey respondents (78.6%) reported using PfH, but less than one-third (31.8%) used the intervention with every patient. The PfH training supports the implementation of the intervention; however, challenges were experienced in clinician engagement. Tailored strategies to recruit and train clinicians providing care to HIV-positive patients are required.